The Effect Of Advertising, Brand Image And Product Variations On Purchase Decisions On Mizone Drink in Sanden District, Bantul Regency - Anindita Imam Basri; Murti Sumarni; Anita Bella Susilowati; Kasnowo Kasnowo (Universitas Kristen Indonesia Toraja, 2022)
This look at objectives to have a look at the effect of advertising, brand image, and product cariations on purchasing decisions on Mizone drinks in Sanden District, Bantul Regency. This sort of research is quantitative research using a sample of 80 respondents. The sampling technique in this observe changed into the usage of purposive sampling and the data collection method turned into changed into the usage of a questionnaire. The results of the look at display that advertising partially has a positive and significant impact on purchasing decisions with a regression coefficient of 0.312 and a significant value of 0.000. brand image partially has a positive and a significant effect on purchasing decisions with a regressions coefficient of 0.301 and a significant value of 0.004. Product variations partially have a positive and significant cost of 0.000. advertising and marketing, brand image, and product variations on purchasing decisions with a significant value of 0.004. Consequently, all the hypotheses of this examine have been universal.